A metaphor analysis of EFL graduate students’ beliefs about an EAP textbook - Shi, Hong (Frontiers in Education, 2022)
This study aimed to evaluate an English for Academic Purposes (EAP) textbook by examining English as a Foreign Language (EFL) graduate students’ beliefs about the textbook through metaphor analysis in a Chinese university setting. This is mainly a descriptive research in nature, and a qualitative research method was employed, supplemented by a quantitative method. The participants of the study are a total of 147 first-year EFL graduate students from a public university in the city of Beijing, China. This evaluation revealed that the EAP textbook provided joy, security, grit, and curiosity for theses students, and at the same time, it was reported as old-fashioned, exam-oriented and teacher-directed. It would be more appropriate with some modifications and also with some additional materials to meet the needs of the EFL graduate students, and some possible implications for teachers and researchers were also suggested in the study.